2019
DOI: 10.1038/s41419-019-1666-2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene RACGAP1P activates RACGAP1/Rho/ERK signalling axis as a competing endogenous RNA to promote hepatocellular carcinoma early recurrence

Abstract: Accumulating evidence has indicated crucial roles for pseudogenes in human cancers. However, the roles played by pseudogenes in the pathogenesis of HCC, particularly HCC early recurrence, still incompletely elucidated. Herein, we identify a novel early recurrence related pseudogene RACGAP1P which was significantly upregulated in HCC and was associated with larger tumour size, advanced clinical stage, abnormal AFP level and shorter survival time. In vitro and in vivo experiments have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…The RACGAP gene is also the first gene reported as an independent biomarker for HCC recurrence. Wang et al discovered the significant up-regulation of the RACGAP1P pseudogene in HCC, which was related to shortened survival, larger tumor size, elevated AFP level and advanced clinical stage [147]. Luciferase assays and in vivo assays demonstrated that miR-15-5p was sequestered from its endogenous target RACGAP by RACGAP1P, causing increased RACGAP expression and contributing to the RACGAP oncogenic network (Fig.…”
Section: Pseudogenes As Cernasmentioning
confidence: 99%
“…The RACGAP gene is also the first gene reported as an independent biomarker for HCC recurrence. Wang et al discovered the significant up-regulation of the RACGAP1P pseudogene in HCC, which was related to shortened survival, larger tumor size, elevated AFP level and advanced clinical stage [147]. Luciferase assays and in vivo assays demonstrated that miR-15-5p was sequestered from its endogenous target RACGAP by RACGAP1P, causing increased RACGAP expression and contributing to the RACGAP oncogenic network (Fig.…”
Section: Pseudogenes As Cernasmentioning
confidence: 99%
“…Other groups and our team previously showed that competing endogenous RNA (ceRNA) mechanism is a key action mode of pseudogene-derived RNA. 15 , 18 To ascertain whether RP11-480I12.5-004 exerts its roles in breast cancer by ceRNA mechanism, we performed a series of studies. First of all, we investigated the subcellular location of RP11-480I12.5-004 using the lncLocator ( http://www.csbio.sjtu.edu.cn/bioinf/lncLocator/ ).…”
Section: Resultsmentioning
confidence: 99%
“…MS2-RIP assay was employed to determine whether endogenous miR-29c-3p could bind to RP11-480I12.5-004, CDK6, and AKT3 according to the previous reports using EZ-Magna RIP kit (Millipore) in accordance with the manufacturers' instructions. 18,46…”
Section: Ms2-rip Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The protein interaction network identified nine key genes [RAD51 (29), KIF4A (30), RACGAP1 (31), SPAG5 (32), HMMr (33), cdc25c (34), cKS2 (35), SHcBP1 (36) and ERCC6L (37)] that interacted strongly with CENPM mRNA. Subsequently, the functions of these nine genes (38)(39)(40)(41)(42)(43)(44)(45)(46) were profiled in various types of cancer and it was identified that all of them have been reported to accelerate the progression of cancer, including BC and hepatocellular carcinoma (29)(30)(31)(32)(33)(34)(35)(36)(37). RT-qPCR demonstrated that the expression levels of five of the nine genes, ERCC6L, CKS2, KIF4A, SPAG5 and CDC25C, were increased in MCF7 cells with elevated CENPM expression, implying that cenPM may promote tumor progression by controlling the expression of these five genes.…”
Section: Discussionmentioning
confidence: 99%